Differentially expressed and new non-protein-coding genes from a Carica papaya root transcriptome survey - Porter, B.W.; Aizawa, K.S.; Zhu, Y.J.; Christopher, D.A.
This study surveyed the root transcriptome of papaya (Carica papaya L.)to identify tissue-regulated genes for promoter isolation. A cDNA library constructed from C. papaya roots was screened using three different methods, and isolated clones were evaluated for expression in roots, leaves, hypocotyls, flowers, and fruit. Homology based functional classification revealed cDNAs for genes associated with defense, beneficial plant-microbe interaction, abiotic stress, and plant development. Homologs associated with plant defense included a hypersensitive-induced response protein, a pathogen-inducible tyrosine-rich hydroxyproline-rich glycoprotein, and two unique peroxidases that have predominate root and hypocotyl-root transcript abundance. A basic leucine zipper protein homologous to the developmental regulatory liguleless2 maize gene was identified and found to exhibit root-specific expression. Of particular interest were three differentially expressed non-protein-coding RNAs (npcRNAs)that lack obvious open reading frames and are predicted to form stable, complex secondary structures. One npcRNAwas found to have specific hypocotyl and root expression. Another exhibits moderate expression in flowers and, interestingly, was found to have three alternative splice variants, two of which appear to be derived from a sequential splicing pathway. The novel npcRNAs have no database sequence homology and are proposed to be new genes. A fourth npcRNA contains a 21 bp sub-region within a 2.7 kb transcript with complementary downstream sequence that is identical to the microRNA MIR162a, suggesting that this is a large, primary microRNA (pri-miRNA)transcript. This is one of only a few pri-miRNA sequences available for a MIR162a ortholog, and it can be used to investigate pri-miRNA evolution and function. The genes with tissue-regulated expression identified here will provide regulatory elements for bioengineering papaya, while the novel non-coding transcripts are candidates for further investigation to explore gene function and miRNA evolution.
Keywords: RNA SECONDARY STRUCTURE; PRIMARY MICRORNA; PRECURSOR MICRORNA; MICRORNA; NON-PROTEIN-CODING RNA; ALTERNATIVE SPLICING